Recent efficacy of modified right vertical infra-axillary thoracotomy for ventricular septal defects in pediatric patients with younger age and Low body weight - Zhang, Heqi; Cao, Hua; Liang, Weijie; Fan, Taibing (Frontiers in Pediatrics, 2026)
ObjectiveTo evaluate the safety and efficacy of a modified right vertical infra-axillary thoracotomy (MRVIAT) technique for treating ventricular septal defects (VSD) in infants younger than six months. and low body weight (≤5 kg).MethodsFrom January 2020 to December 2024, the study included 204 infants who underwent MRVIAT and 62 infants who underwent median sternotomy (MS). General, perioperative, and follow-up data were analyzed retrospectively.ResultsOperation time, intraoperative bleeding, 24-h postoperative chest tube drainage, mechanical ventilation time, postoperative intensive care unit time, extubation rate within 24 h postoperatively, hospital costs, and incision length were shorter in the MRVIAT group than in the MS group (P < 0.05). Peak airway pressure, lung dynamic compliance (Cdyn), and oxygenation index were similar in both groups at preoperative and postoperative time points (P > 0.05). There were no deaths in either group, and there was no significant difference in complication rates (P > 0.05). At 60 months (with a median follow-up of 25 months), two cases of sternal deformity occurred in the MS group, but none occurred in the MRVIAT group.Conclusionventricular septal defect repair by MRVIAT in younger children with low body weight is less invasive. It provides good incision exposure, does not affect pulmonary function, reduces intraoperative bleeding and postoperative hospital stay and costs, and facilitates rapid recovery. This procedure is safe and effective and can be considered an alternative to median sternotomy.